2009
DOI: 10.1177/1541204009333797
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy in Adolescence Predicts Official Reports of Offending in Adulthood

Abstract: The present study examines the incremental predictive utility of psychopathy assessed at age 13 using the Childhood Psychopathy Scale (CPS) in predicting official records of arrests and convictions between the ages of 18 and 26. Data from 338 men from the middle sample of the Pittsburg Youth Study were used. A variety of control variables were included: demographics (race, family structure, SES, and neighborhood SES), parenting (physical punishment, inconsistent discipline, lax supervision, and low positive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 57 publications
(87 reference statements)
4
57
0
2
Order By: Relevance
“…With regard to psychopathic personality traits, recent research has demonstrated that youth psychopathy is an important risk factor for future antisocial and violent offending behaviors (Gretton, Hare, & Catchpole, 2004;Lynam, Miller, Vachon, Loeber, & Stouthamer-Loeber, 2009;Salekin, 2008). Other researchers have found that callous and unemotional traits predicted aggression and conduct problems in adolescents (Frick, Cornell, Berry, Bodin, & Dane, 2003).…”
Section: Youth Gangs and Delinquencymentioning
confidence: 99%
“…With regard to psychopathic personality traits, recent research has demonstrated that youth psychopathy is an important risk factor for future antisocial and violent offending behaviors (Gretton, Hare, & Catchpole, 2004;Lynam, Miller, Vachon, Loeber, & Stouthamer-Loeber, 2009;Salekin, 2008). Other researchers have found that callous and unemotional traits predicted aggression and conduct problems in adolescents (Frick, Cornell, Berry, Bodin, & Dane, 2003).…”
Section: Youth Gangs and Delinquencymentioning
confidence: 99%
“…Several studies find that CU traits are moderately stable from late childhood to early adolescence (Frick, Kimonis, Dandreaux, & Farrell, 2003;Munoz & Frick, 2007), and from adolescence to adulthood (Lynam, Caspi, Moffitt, Loeber, & Stouthamer-Loeber, 2007;Lynam, Miller, Vachon, Loeber, & Stouthamer-Loeber, 2009). Compared with youth low on CU traits, antisocial youth high on CU traits present with a particularly severe and stable pattern of conduct problems and delinquent behavior (Frick, Cornell, Barry, Bodin & Dane, 2003;Frick, Stickle, Dandreaux, Farrell, & Kimonis, 2005;Loney, Taylor, Butler, & Iacono, 2007), tend to show greater substance-related delinquency (Taylor & Lang, 2006), and show higher rates of aggression, and violent and sexual offending (Caputo, Frick, & Brodsky, 1999;Frick & White, 2008).…”
Section: Violence Exposure Mediates the Relation Between Callous-unemmentioning
confidence: 99%
“…Amongst the risk factors for youth or juvenile delinquency the most commonly reported are demographic characteristics (e.g. age, gender, race); as well as aggression; deviant peer association, antisocial attitudes and behaviour; low intelligence (Bartol & Bartol, 2009;Farrington, 2002;Lynam, Miller, Vachon, Loeber, & Stouthamer-Loeber, 2009). Also some individual characteristics commonly associated with youth delinquency are impulsiveness, aggression, lack of empathy, lack of emotional control and cruel behaviour are risk factors associated with youth delinquency (Farrington, Loeber, Jolliffe, & Pardini, 2008;Piquero, Farrington, & Blumstein, 2007;Loeber, Green, & Lahey, 2003).…”
Section: Introductionmentioning
confidence: 99%